Bears on wheels - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012 (New York : Random House, 2014)
An acrobatic act begins with one bear on a unicycle and ends with twenty-one bears and sixteen wheels flying through the air.
"Originally published in slightly different form by Random House Children's Books, in 1969."
Keywords: Acrobatics -- Fiction; Bears -- Fiction; Counting; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / Concepts / Counting & Numbers